The Relationship of Oral Hygiene Habit with Halitosis Perception Among the Users of The Fixed Orthodontic - Andan, Annisaa Nur Aulia, Stheril; Karlina,; Adventa, Yosefin; Fadhila, Azalia Izzah; Dianita, Aura Zathirah; Kusumo, Aryo Dwipo (International Journal of Psychosocial Rehabilitation, 2020)
Fixed orthodontic users who have bad oral hygiene habits are possible to have the perception of halitosis or bad breath. Based on research conducted by Bollen & Beikler in 2012, 25% of the world's population experiences halitosis. Based on data from the Ministry of Health Riskesdas in 2018, the prevalence of orthodontic users is 0.3%. The existing treatment for the problem of halitosis in fixed orthodontic users is proper tooth-brushing techniques, a "healthy teeth" diet, and routine appointments to follow up with the dentist, however, modification of existing dietary and oral hygiene habits is not easy to achieve and requires special efforts. On the part of dentists and patients, as well as the lack of discipline of fixed orthodontic users to maintain oral hygiene properly, can make some users experience halitosis. Therefore, further surveys are needed regarding the relationship between oral hygiene habits with the perception of halitosis in fixed orthodontic users to prevent halitosis. Objective: To analyze the correlation between oral hygiene habits and the perception of halitosis in fixed orthodontic users. Methods: Data were collected from distributing questionnaires toward fixed orthodontic users. Then, the normality test was done using Shapiro-Wilk and then the Spearman analysis test was also performed. Results: The percentage of respondents who had good oral hygiene habits was 48% while the bad ones were 52%. The percentage of respondents who had positive halitosis perceptions was 64.7% while the negative was 35.3%. The correlation coefficient of the two variables showed a weak correlation. Conclusion: There was a correlation between oral hygiene habits with the perception of halitosis.